ANALYSIS OF FINANCIAL PERFORMANCE PRE AND DURING THE CORONA VIRUS PANDEMIC OF BANKING COMPANIES - Winata, Catherine Liusca; Hastuti, Rini Tri (International Journal of Application on Economics and Business, 2025)
The Corona virus pandemic has spread to several countries, one of which is Indonesia. The impact of the Corona virus pandemic has disrupted several industrial sectors, including banking, which is the driving force of a country's economy and economic growth in Indonesia has experienced a decline during the pandemic.The aim and purpose of this study is to evaluate and analyze the comparison of financial performance before and during the Corona outbreak in companies in the banking sector that have been listed as the Stock Exchange in Indonesia (IDX) from 2018 to 2021. The sample method used is purposive sampling according to predetermined criteria, with a total of 11 companies as samples. Proxies used to measure financial performance comparisons include Return on Assets, Operating Expenses to Operating Income, and Loan to Deposit Ratio. Hypothesis testing was performed using SPSS Statistics 25 software with a Paired Sample t-Test difference test. The results of the study stated that there was a difference between the period before and when the Corona virus took place in the ratio of financial performance measured using the proxy Return on Assets, Operating Expenses to Operating Income, and Loan to Deposit Ratio in banking sector companies listed on the IDX.